Subiektywne zdrowie osób z niepełnosprawnością fizyczną = Subjective health of people with physical disabilities - Petrová, Nad'a (Vilnius: Mykolas Romeris Universitetas)
The paper deals with the topic of subjective health as a significant value for every person. The research is focused on the analysis of subjective perception of health of people with congenital and acquired physical disabilities. The used research tool is the WHODAS 2.0 which is standardized questionnaire focuses on subjective health. The research sample consist of 50 individuals with physical disabilities from the Czech Republic.
Keywords: zdrowie; subiektywne zdrowie; WHODAS 2.0; jednostka z niepełnosprawnością fizyczną; wrodzone upośledzenie fizyczne; nabyte upośledzenie fizyczne; health; subjective health; person with physical disabilities